A new deal for cancer : lessons from a 50 year war - Gluck, Abbe R.; Fuchs, Charles S.; Rusyn, Eugene; Mukherjee, Siddartha; Oyer, Randall A.; Aakhus, Erin O.; Yabroff, K. Robin; Benz, Edward J., Jr; McAneny, Barbara; Nguyen, Matt K.; Brawley, Otis Webb; Polite, Blase N.; et al. (Public Affairs, 2021)
"The longest war in the modern era, longer than the Cold War, has been the war on cancer. Cancer is a complex, evasive enemy, and there was no quick victory in the fight against it. But the battle has been a monumental test of medical and scientific research and fundraising acumen, as well as a moral and ethical challenge to the entire system of medicine. In A New Deal for Cancer, some of today's leading thinkers, activists, and medical visionaries describe the many successes in the long war and the ways in which our deeper failings as a society have held us back from a more complete success. Together they present an unrivaled and nearly complete map of the battlefield across dimensions of science, government, equity, business, the patient provider experience, and more, documenting our emerging understanding of cancer's many unique dimensions and offering bold new plans to enable the American health care system to deliver progress and hope to all patients." --Page [2] of cover.